Alto da Serra do Botucaraí - Ana Maria de Aveline Bertê; Bruno de Oliveira Lemos; Grazieli Testa; Marco Antonio Rey Zanella; Suzana Beatriz de Oliveira (Boletim Geográfico do Rio Grande do Sul, 2016)
.